EFFECT OF ANTIMALARIA HERBAL SAMBILOTO (Andrographis paniculata Nees) ON MORPHOLOGY CHANGES OF DEVELOPMENT AND PARASITE Plasmodium Falciparum - ERIKA MARIA RESI; CHRISTINE JANSE KATJIE EKAWATI (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
The emergence of resistance of Plasmodium that infect humans against malaria eradication Artemisinin add to the difficulty. Therefore it is necessary to search for new antimalarial drugs derived from natural or synthetic materials other than the vaccine have not been successful. The results of fractionation or isolation of the ethanol extract of bitter herbs (Andrographis paniculata Nees) and ethanol extracts obtained andrographolide compound which is the main active substance of bitter herbs belonging to the lactone. Test antimalarial activity of ethanol extract and andrographolide compounds against Plasmodium falciparum in vitro studies suggest that and rographolide compound said to have anti-malarial activity as compared to active ethanol extract with IC50 values of 0.220 μg/ml. Test the effect of andrographolide compounds bitter herbs (Andrographis paniculata Nees) on the development and morphology of the parasite stages of P. falciparum in vitro studies suggest that there are barriers to the development stage of the parasitic stage and schizont stage tropozoit be schizont stage into ring -stage parasites grow and cause an abnormal morphology. The conclusion of this study is that the antimalarial herb bitter (Andrographis paniculata Nees) especially andrographolide compound said to have anti-malarial activity as in vitro , causing developmental delays or obstacles stage parasites grow and cause an abnormal morphology. Therefore antimalarial bitter herbs in this compound andrographolide potentially be used as an antimalarial drug that is new blood skizontisidal.